PENGARUH NILAI BUDAYA ASIA DALAM KERAMAHTAMAHAN ASIA - B. Syarifuddin Latif (Jurnal Ilmu dan Budaya, 2019)
Asian hospitality has gained a reputation for excellence in quality of facilities and services over the past decade. The unique, lovely ways of Asian hospitality spring from its strong historical and cultural background. Asian cultures and their peoples have special hand-making skills and are detail orientated which can be seen from the products produced and services provided by Asian organizations. They have a strong cultural education in the sense of " kindness and giving ". This makes them well suited for providing the required unique services and able to respond to the demands of this new century. This paper aims to enhance the understanding of the influence that Asian cultures and values have on Asian hospitality. In addition, it focuses how it manifests itself in the uniquely Asian characteristic in the hospitality industry. The findings illustrate that Asian hospitality is well accepted worldwide and that a continued fine tuning is needed to create the perfect Asian hospitality experience. It is of an interest to both practitioners and academic educators in the hospitality management field.